Persistence of Real Exchange Rates in the Central and Eastern European Countries. Issue 3 (3rd May 2016) - Baharumshah, Ahmad Zubaidi; Soon, Siew-Voon; Fountas, Stilianos; Mohamad Shariff, Nurul Sima
Abstract: We investigate the mean reversion in real exchange rates for Central and Eastern European countries. We use point and confidence interval estimates from the Phillips et al .'s (2001) local-persistent model as our preferred measures of the persistence of real exchange rates. We find that the adjustment to purchasing power parity is more rapid after accounting for structural breaks, with half-life deviation from parity below 18 months, which is consistent with the explanation based on nominal rigidities. The estimated narrow confidence intervals for the half-lives invalidate the purchasing power parity puzzle for transition and some core European Union countries. The novelty of our results lies in the finding of strong evidence for purchasing power parity as the local-persistent model produces shorter half-lives and much narrower corresponding confidence intervals than those obtained by standard Dickey-Fuller and local-to-unity models. Our evidence for PPP suggests that the transition countries have maintained their long-run competitiveness against their trading partners.